A new one‐dimensional nickel metal–organic framework: catena‐poly[[[diaquabis(4‐{[(1‐phenyl‐1H‐tetrazol‐5‐yl)sulfanyl]methyl}benzoato‐κO)nickel(II)]‐μ‐4, 4′‐bipyridine‐κ2N:N′] monohydrate]. Issue 3 (12th February 2014) - Geng, Aijing; Zhang, Qingfu; Wang, Jiajia; Zhang, Haina; Sun, Dezhi
<x xml:space="preserve">Abstract</x> The title complex, {[Ni(C15H11N4O2S)2(C10H8N2)(H2O)2]·H2O}n, was synthesized by the reaction of nickel chloride, 4‐{[(1‐phenyl‐1H‐tetrazol‐5‐yl)sulfanyl]methyl}benzoic acid (HL) and 4, 4′‐bipyridine (bpy) under hydrothermal conditions. The asymmetric unit contains two half NiII ions, each located on an inversion centre, two L− ligands, one bpy ligand, two coordinated water molecules and one unligated water molecule. Each NiII centre is six‐coordinated by two monodentate carboxylate O atoms from two different L− ligands, two pyridine N atoms from two different bpy ligands and two terminal water molecules, displaying a nearly ideal octahedral geometry. The NiII ions are bridged by 4, 4′‐bipyridine ligands to afford a linear array, with an Ni...Ni separation of 11.361 (1) Å, which is further decorated by two monodentate L− ligands trans to each other, resulting in a one‐dimensional fishbone‐like chain structure. These one‐dimensional fishbone‐like chains are further linked by O—H...O, O—H...N and C—H...O hydrogen bonds and π–π stacking interactions to form a three‐dimensional supramolecular architecture. The thermal stability of the title complex was investigated via thermogravimetric analysis.